(untitled) (e-Journal of Linguistics, 2026)
This study examines topicalization strategies in the framework of information structure in Javanese from a diachronic perspective. The main focus of the research is on three constructs: pseudo-cleft and hanging topic as well as the shift from object topicalization of middle Javanese to contemporary Javanese. The method used is corpus-based descriptive qualitative. Middle Javanese data was taken from three written literary texts, while contemporary Javanese data is taken from authentic oral data in the form of transcripts of Javanese sermon podcasts. The analysis was carried out through the stages of structural identification, pragmatic function mapping, and diachronic comparison. The results of the study show three main findings. First, the pseudo-cleft in contemporary Javanese serves as a marker of focus, contrast, and empathy-didactic in the theological register. Second, the hanging topic in contemporary Javanese serves as a marker of thematization, theological politeness on the referent of God, and the organization of oral discourse. Third, there is a shift in object topicalization from middle Javanese which is narrative stylistic without resumptive pronouns, to a productive hanging topic in contemporary Javanese with resumptive -e for cohesion. Diachronically, the study also found that the process of grammaticalization of the iku copula became a mandatory cleft marker in contemporary Javanese.